2018
DOI: 10.1111/conl.12457
|View full text |Cite
|
Sign up to set email alerts
|

CITES‐listed sharks remain among the top species in the contemporary fin trade

Abstract: Trade-driven overexploitation threatens many sharks. Twelve of the world's most vulnerable shark species have been listed on the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) to regulate internationally traded products such as meat and dried fins. CITES records indicate that Hong Kong was the world's top legal importer of dried fins from listed sharks in 2015 (N = 8 species at that time), but traded a relatively small volume, with a few partners, in a small number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(111 citation statements)
references
References 20 publications
6
101
2
Order By: Relevance
“…Interestingly, the species composition observed differs markedly from previous assessments of the species composition of the fin trade by Fields et al () and Cardeñosa et al (2018 a ). Both previous studies indicated that > 50% of fin‐trimmings were from pelagic species (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, the species composition observed differs markedly from previous assessments of the species composition of the fin trade by Fields et al () and Cardeñosa et al (2018 a ). Both previous studies indicated that > 50% of fin‐trimmings were from pelagic species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens and products from CITES Appendix II species (and others including silky and pelagic threshers, also found in the small fins) must be exported with a set of permits to certify that trade is not detrimental to the survival of the species, it is traceable through the supply chain, and that specimens were legally obtained (Vincent et al ., ). Cardeñosa et al (2018 a ) found that CITES‐listed shark species remain among the top species in the contemporary fin trade, with these hammerhead species representing the fourth and fifth most common species overall. The evidence presented by Cardeñosa et al (2018 a , b ) and this study, suggests that fins from all size classes of these CITES‐listed species are still part of the international trade, and are among the most common in the Hong Kong shark fin retail markets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing evidence that European eels are illegally exported from the EU to East Asia (Musing et al, ; Stein et al, ), and one of the major problems for law enforcement officers is the inability to identify the species of traded live eels or meat, in a timely manner (Musing et al, ). While commonly used wildlife forensics tools (e.g., DNA barcoding) have proven useful to detect illegal wildlife trade (Cardeñosa et al, ; Gonçalves, Oliveira‐Marques, Matsumoto, & Miyaki, ; Stein et al, ), most of these tools require transferring tissue samples to a laboratory away from the port‐of‐entry and going through complex process of DNA barcoding, which can take hours or days. A more portable, faster, and potentially more cost‐effective approach for detection of illegal wildlife trade that can be deployed at the port‐of‐entry is real‐time polymerase chain reaction (rtPCR).…”
Section: Introductionmentioning
confidence: 99%